Scientific Attitudes in Islamic Education Learning: Relationship and the Role of Self-Efficacy and Social Support - Latipah, Eva; Kistoro, Hanif Cahyo Adi; Khairunnisa, Imaniyah (EDUKASIA, 2020)
Scientific attitude in Islamic education learning is a demand in the newest curriculum. Psychological factors that determine it is self-efficacy and social support. This study aims to examine correlation between self-efficacy and social support with students' scientific attitudes in Islamic education learning, partially and simultaneously. Subjects were 152 Madrasa Ibtidaiyah students. Instruments used are scientific attitude, self-efficacy, and social support scales. Data analysis techniques used regression analysis. Results showed that there’s a significant positive correlation between self-efficacy and students’ scientific attitude in Islamic education learning with r=0.367 and p=0.000 (p<0.05). There’s a significant positive correlation between social support and scientific attitude in Islamic education learning with r=0.381 and p=0.000 (p<0.05). There’s a positive and significant correlation between self-efficacy and social support simultaneously with scientific attitude in Islamic education learning with F=18.222 and p=0.000 (p<0.05).